Immunogenicity and Safety of COVID-19 Vaccines in Patients Receiving Renal Replacement Therapy: A Systematic Review and Meta-Analysis - Ma, Becky Mingyao; Tam, Anthony Raymond; Chan, Kam Wa; Ma, Maggie Kam Man; Hung, Ivan Fan Ngai; Yap, Desmond Yat Hin; Chan, Tak Mao (Frontiers in Medicine, 2022)
Background: Systematic data on the efficacy and safety of COVID-19 vaccine in patients on renal replacement therapy (RRT) remains limited. We conducted a meta-analysis on the efficacy and safety of COVID-19 vaccine in patients on RRT. Methods: Eligible studies were identified by systematic literature search in four electronic databases. Twenty-seven studies (4264 patients) were included for meta-analysis. 99% patients received mRNA vaccine. Results: Patients on RRT showed inferior seropositivity after two-dosed COVID-19 vaccine, 44% lower than the general population. Kidney transplant recipients (KTRs) had significantly lower seropositivity than patients on haemodialysis (HD) or peritoneal dialysis (PD) (26.1% vs. 84.3% and 92.4% respectively, p<0.001 for both). Compared with healthy controls, KTRs, HD and PD patients were 80% (95% CI: 62-99%), 18% (95% CI: 9-27%) and 11% (95% CI: 1-21%) less likely to develop antibodies after vaccination (p<0.001, <0.001 and 0.39 respectively). In KTRs , every 1% increase in using mycophenolate was associated with 0.92% reduction in seropositivity (95% CI: -1.68, -0.17, p=0.021) at population level. The overall adverse event rate attributed to vaccination was 2.1%. Most events were mild. Conclusion: Patients on RRT, particularly KTRs, had significantly reduced antibody response after two-dosed COVID-19 vaccination. Vaccination is generally well tolerated.